Nutrição de Tilapia melanopleura Dumeril - Rodrigues de Souza, José; Ferreira Vilela , Evaldo (Revista Ceres, 2025)
The weight gain of Tilapia melanopleura Dumeril raised in artificial -ponds under four feed treatments was studied in Viçosa, Minas Gerais. Cotton seed cake gave the best results. Weight gained using normal corn, opaque-2 corn and soybean meal did not show statistical differences.